Proven anti-virulence therapies in combating methicillin- and vancomycin-resistant Staphylococcus aureus infections - Bakeer, Walid; Gaafar, Marwa; El-Gendy, Ahmed O.; El Badry, Mohamed. A.; Khalil, Mona G.; Mansour, Abdallah Tageldein; Alharbi, Nada K.; Selim, Heba M. R. M.; Bendary, Mahmoud M. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionDespite years of efforts to develop new antibiotics for eradicating multidrug-resistant (MDR) and multi-virulent Methicillin-Resistant Staphylococcus aureus (MRSA) and Vancomycin-Resistant Staphylococcus aureus (VRSA) infections, treatment failures and poor prognoses in most cases have been common. Therefore, there is an urgent need for new therapeutic approaches targeting virulence arrays. Our aim is to discover new anti-virulence therapies targeting MRSA and VRSA virulence arrays.MethodologyWe employed phenotypic, molecular docking, and genetic studies to screen for anti-virulence activities among selected promising compounds: Coumarin, Simvastatin, and Ibuprofen.ResultsWe found that nearly all detected MRSA and VRSA strains exhibited MDR and multi-virulent profiles. The molecular docking results aligned with the phenotypic and genetic assessments of virulence production. Biofilm and hemolysin productions were inhibited, and all virulence genes were downregulated upon treatment with sub-minimum inhibitory concentration (sub-MIC) of these promising compounds. Ibuprofen was the most active compound, exhibiting the highest inhibition and downregulation of virulence gene products. Moreover, in vivo and histopathological studies confirmed these results. Interestingly, we observed a significant decrease in wound area and improvements in re-epithelialization and tissue organization in the Ibuprofen and antimicrobial treated group compared with the group treated with antimicrobial alone. These findings support the idea that a combination of Ibuprofen and antimicrobial drugs may offer a promising new therapy for MRSA and VRSA infections.ConclusionWe hope that our findings can be implemented in clinical practice to assist physicians in making the most suitable treatment decisions.